2019
DOI: 10.1177/0379572118816459
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Fruit and Vegetable Consumption Among Rural Indian Women of Reproductive Age

Abstract: Background Micronutrient insufficiencies are a serious public health problem among women of reproductive age in Low and Middle Income Countries including India, adversely affecting maternal health and economic productivity, and child growth and educational outcomes. Fruit and vegetables are important sources of micronutrients and consumption of these foods is less than recommendations. Objective To identify perceived barriers and facilitators to fruit and vegetable consumption among women of reproductive age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…27 The decline in demand for indigenous vegetables that don't require large amounts of water or agri-chemicals was talked about by consumers. 24 These findings are comparable with a study among tribal households in Jharkhand, India, in which it was found that overall intakes of indigenous foods were low, yet those women who did consume them had higher intakes of calcium and iron than those who did not. 28 Addressing this decline in demand through promoting the cultivation of these plants and educating consumers may lead to a "win-win" scenario in that local production of, and demand for, nutritious foods is increased.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…27 The decline in demand for indigenous vegetables that don't require large amounts of water or agri-chemicals was talked about by consumers. 24 These findings are comparable with a study among tribal households in Jharkhand, India, in which it was found that overall intakes of indigenous foods were low, yet those women who did consume them had higher intakes of calcium and iron than those who did not. 28 Addressing this decline in demand through promoting the cultivation of these plants and educating consumers may lead to a "win-win" scenario in that local production of, and demand for, nutritious foods is increased.…”
Section: Discussionsupporting
confidence: 84%
“…We held 12 interviews with reproductive-age women (18-40 years) living in 8 villages surrounding Wardha during which we asked about consumption of the exemplar foods and about how they accessed these foods. 24 Based on their responses, we identified and made contact with the vendors of these foods. We interviewed a purposive sample of these vendors based on where they sold their products (with one vendor serving each of the 8 villages).…”
Section: Methodsmentioning
confidence: 99%
“…However, while poverty and unstable incomes are likely to play a large part in the link between food security and diet diversity and quality, there may be other confounding factors among those who are food insecure. These could include: time and resources available to prepare food; increased convenience and availability of ultra-processed foods; taste preference, particularly if any 'healthier' options such as fruit and vegetables are not fresh or have been poorly stored; marketing and advertising of ultra-processed foods or an unhealthy food environment (39,40) (Ersze et al, Public Health Nutrition, in press). The food environment in settings such as Soweto has to date been under-studied and will be a focus of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Geographically, the spread of underweight appears to be higher among adult women than it is for adult men. Parallel to the low allocation of household foods due to gendered norm, where female members receive comparatively less energy than the male members (38) , some studies have reported that women in some regions of the country are restricted to eat certain kind of foods (e.g., fruits and vegetables, animal protein-based foods) due to, for instance, social taboos or religious beliefs, with the result that women are deprived of the necessary nutrients (39) .…”
Section: Discussionmentioning
confidence: 99%